Witamy w Gdańsku 11-12 czerwca 1987 (Gdańsk : [s.n.], 1987)
Plakat z pielgrzymki Jana Pawła II do Gdańska w czerwcu 1974 r.
Keywords: Jan Paweł -- II -- (papież ; -- 1920-2005) -- podróże -- Polska -- Gdańsk -- plakaty